Preparation of molecular sieves with antimicrobial properties from pillared clays and silver and copper nanoparticles - Lucero Lucas, Gisella Liliana (Pontificia Universidad Católica del Perú, 2017)
Aluminum pillared clays (Al–PILC) modified with silver and copper nanoparticles were prepared in order to get a material with antimicrobial properties against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). Al-PILC were characterized by X - ray diffraction (XRD), Scanning electron microscopy (SEM) with energy – dispersive X - ray spectroscopy (EDX), the Boehm titration and the nitrogen sorption method. According to these techniques, the pillaring process increased the interlayer distance in 8.7 Å and it corresponds approximately to the size of the Keggin´s ion. The surface area of the natural clay grew from 56 m2/g to 195 m²/g for the Al-PILC after its calcination because new micropores arise. Silver and copper nanoparticles were prepared by a chemical reduction method using D – glucose and ascorbic acid as reductor agents. Silver and copper nanoparticles were analyzed by UV – Visible spectroscopy and SEM – EDX. In addition, the silver concentration in a suspension was determined by atomic absorption spectroscopy. Nanoparticles were spherical and their particle size was between 15 and 33 nm and they were immersed in a starch matrix. Synthesis conditions (frequency and temperature) had an influence on the particle size which increased with higher frequency (80 kHz) and temperature (59°C). Copper nanoparticles were prepared using different volume of ascorbic acid; 1.6 ml produced smaller particles (20 – 86 nm); however, this range of particle size was not reproducible. For that reason, in the microbiological experiments were used commercial copper nanoparticles with a size between 27 nm and 34 nm. Silver al copper nanoparticles were incorporated to Al–PILC by impregnation and the modified clays were characterized by SEM –EDX. From the microbiological experiments, the silver and copper suspensions reduce the number of S. aureus and E. coli alive cells in comparison to the number of alive cells in the sample without modified clay and nanoparticles.
Keywords: Ingeniería química; Nanotecnología; Microbiología--Experimentos; Rayos X; https://purl.org/pe-repo/ocde/ford#2.03.01